MODEL DIRECT INSTRUCTION UNTUK MENGEMBANGKAN KEMAMPUAN PENETAPAN ANGKA KREDIT GURU SEBAGAI UPAYA PENINGKATAN KOMPETENSI CALON GURU SEJARAH PROFESIONAL - Ipong Jazimah; Arifin Suryo Nugroho (Universitas Muhammadiyah Purwokerto, 2020)
ABSTRACT The problems in this study are 1) How to apply the direct instruction model to develop the ability to determine teacher credit points as an effort to increase the competence of prospective professional history teachers 2) What are the results of improving student abilities that have been achieved by applying the direct instruction model 3) What are the obstacles faced and how to attempt to solve it. This research uses a qualitative approach. Data sources consist of documents and informants. Documents in the form of books, magazines, journals, pretest and posttest results. Data were collected by recording documents, observations, and interviews. The data validity was done by means of data triangulation. Data analysis used interactive analysis with three stages of analysis, namely data reduction, data presentation, and drawing conclusions. This research results in the conclusion that 1) The direct instruction learning model can improve understanding of the material, 2) Studying the material for teacher credit scores makes education study program students more creative and innovative in creating new ideas, 3) The need for educational study program students to be equipped with the ability material for teacher credit scores so that later when they become teachers they become professional teachers with teacher professional rank lines. Keywords: Direct instruction learning model, teacher credit score